Parkinsonism beyond Parkinson's disease - Stamelou, Maria; Hoglinger, Gunter U. (International review of neurobiology ;, 2019)
Parkinsonism beyond Parkinson's Disease, Volume 149, the latest release in the International Review of Neurobiology series, highlights new advances in the field, with this new volume presenting interesting chapters on a variety of topics, including How to approach a patient with parkinsonism - red flags for atypical parkinsonism, The 'classic' atypical parkinsonian disorders, Classification of atypical parkinsonism per pathology vs. phenotypes, Progressive supranuclear palsy, Corticobasal degeneration, Multiple system atrophy, Atypical parkinsonism in other sporadic and genetic neurodegenerative diseases, Sporadic 'Atypical' Parkinson's disease, and much more. --